Chemical investigation and microbial activity of Tinospora cordifolia miers (Journal of Bio-Science, 2014)
Context: Plants have been used in treating human diseases for thousands of years. Medicinal plant drug discovery continues to provide new and important leads against various pharmacological targets including cancer, malaria, HIV/AIDS, Alzheimer's, and pain. Objectives: The chemical investigation, antimicrobial activity and toxicity of the active principles isolated from the plant. Materials and Methods: The rectified spirit extract of the fresh stem of the plant Tinospora cordifolia was fractionated using standard chromatographic techniques to afford several fractions. The fraction TC-1 was purified by crystallization and screened. FTIR, 1H NMR, 13C NMR spectral analyses were performed to characterize the compound. The antibacterial and antifungal activities of TC-1 were observed by Disc diffusion method against a number of pathogenic bacteria and fungi. Standard antibiotics Kanamycin (30?g/disc) and Fluconasol (500 ?g/disc) were used respectively for comparison. The minimum inhibitory concentration (MIC) of the compound TC-1 was carried out by the Serial Dilution Technique. The compound also showed significant activity against the brine shrimp nauplii. Results: The compound TC-1 showed promising antibacterial and antifungal activities against all tested organisms.The minimum inhibitory concentration (MIC) of TC-1 against Bacillus megaterium and Salmonella typhi-A was found to be 128?g/ml in nutrient broth medium. The value of medium lethal concentration, LC50 (9.34 ?g/ml) indicated the high toxic effect of the compound TC-1. Conclusion: It may be concluded that the compound TC-1 is an alkaloid having significant activities. DOI: http://dx.doi.org/10.3329/jbs.v20i0.17737 J. bio-sci.  20:  153-160, 2012